The IMF and The Poor. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
The IMF is increasingly emphasizing "high-quality growth" - that is, growth that is sustainable, that is accompanied by appropriate domestic and external balances, that respects the environment, and that is aided by policies that reduce poverty and foster greater equity. This pamphlet focuses on how the IMF works to reduce poverty and improve equity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet